2021
DOI: 10.1186/s12866-021-02193-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genomic characterization of five novel strains of Erysipelotrichaceae from commercial pigs

Abstract: Background Members of the Erysipelotrichaceae family have a high abundance in the intestinal tract of mammals, and have been reported to be associated with host metabolic disorders and inflammatory diseases. In our previous study, we found that the abundance of Erysipelotrichaceae strains in the cecum was associated with the concentration of N-acetylgalactosamine (GalNAc). However, only a few members of Erysipelotrichaceae have been isolated and cultured, and their main characteristics, genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 73 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…N -Lauroylglycine and 2-aminooctanoic acid, two fatty acid metabolites, had negative and positive correlations with ADG, respectively. As a lipoamino acid in the cell membrane of various bacteria, N -lauroylglycine in mouse feces has been positively correlated with Erysipelotrichaceae [ 35 ], which is a family of Gram-positive bacteria with the genomic characteristic of a polysaccharide utilization function [ 36 ]. As for 2-aminooctanoic acid, it has been detected in the serum of pigs as a marker of ractopamine—a growth promoter [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…N -Lauroylglycine and 2-aminooctanoic acid, two fatty acid metabolites, had negative and positive correlations with ADG, respectively. As a lipoamino acid in the cell membrane of various bacteria, N -lauroylglycine in mouse feces has been positively correlated with Erysipelotrichaceae [ 35 ], which is a family of Gram-positive bacteria with the genomic characteristic of a polysaccharide utilization function [ 36 ]. As for 2-aminooctanoic acid, it has been detected in the serum of pigs as a marker of ractopamine—a growth promoter [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, dietary supplements with B. animalis promoted Erysipelotrichaceae_UCG-003 populations in both lumens of the ileum and cecum, which may positively affect the growth performance of pigs. Polysaccharide utilization loci analysis indicated that Erysipelotrichaceae strains may have the ability to utilize plant polysaccharides ( 43 ). Concordantly, pigs fed a diet with high corn-based arabinoxylans increased Erysipelotrichaceae_UCG-002 abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other members of the Erysipelotrichaceae family, to which Ileibacterium belongs, have been reported as being intrinsically resistant to vancomycin. [45][46][47] Considering that mechanisms for resistance against glycopeptide antibiotics like vancomycin can differ greatly between taxa and remain to be fully characterized in all bacteria, 48 it is thus still possible that Ileibacterium is truly resistant to vancomycin.…”
Section: Discussionmentioning
confidence: 99%